Analisis Partisipasi Masyarakat Guna Mendukung Pembangunan Masyarakat di Kota Medan - Sony Tambunan, Toman (Jurnal Publisitas, 2022)
Participation is a form of community involvement or participation in all activities that occur in the life of the community and state. The purpose of this study was to determine the extent of community participation to support community development in the city of Medan. The form of community participation to support community development in Medan City, consists of: First, community participation to support the implementation of Regional Government. Second, community participation to support economic business development. Third, community participation to support community development. The results of the study, it can be concluded that the level of community participation in community development in Medan in 2019 in accordance with the participation phase, it can be seen that at the participation stage for planning that is equal to 84.66 percent are in the category of "Very High", the participation stage for implementation of 77.66 in the "High" category, the participation stage for monitoring or evaluation was 86.33 percent in the "Very High" category, the participation rate for utilization of 77.33 percent was in the "High" category. In total the level of community participation in community development in Medan City in 2019 is in the category of "Very High".